Synthesis and antimicrobial activity of dinaphtho [2,1-b] furan-2-yl-methanone and their oxime derivatives - Kırılmış, Cumhur; Koca, Murat; Servi, Süleyman; Gür, Seher (My University, 2009)
The reaction of 2-hydroxy-1-naphthaldehyde with 1,3-dichloroacetone and potassium carbonate was used to prepare dinaphtho[2,1- b]furan-2-yl-methanone (1) as starting reagents. In order to obtain dinaphtho[2,1- b]furan-2-yl-methanole (2), compound 1 was reduced with Na$BH_4$ . N -oxime derivative of this compound (3) was synthesized by the reaction of the compound 1 with hydroxylamine. Alkyl and acyl substituted N - oxime ethers (4-11) were obtained by the reaction compound 3 with various halogen containing compounds. Compound 12 was obtained by reflux of the compound 11 with hydrazine monohydrate in ethanol. Compound 13 was synthesized by the reaction of the compound 11 with NaOH. The synthesized compounds were tested for antimicrobial activity against Salmonella typhimurium, Escherichia coli, Bacillus subtilis, Candida globrata, and Candida tropicalis. All of the selected compounds showed weak antimicrobial activity against test microorganisms (128- 512 μg/mL).
Keywords: Kimya; Organik; Mikrobiyoloji; Farmakoloji ve Eczacılık